Bacillus Cucumis: A New Source Of L-Methioninase Enzyme With Potential For Cancer Therapy (Applied Biological Research, 2023)
The existing cancer therapies usually target a single pathway, and the associated  side effects and higher costs involved in such mono-target therapies have  necessitated to find alternative treatment strategies. Methionine dependency is  commonly seen in cancer cells cancerwhereas normal cells in absence of methionine  can grow on homocysteine, as they possess intact methionine synthase. So  reducing the level of cancer cell/plasma methionine with the help of L methioninase enzyme looks a very promising therapy to manage the cancer. The  present research was based on rapid screening of soil samples for L methioninase producing microbes using selective media. The selected microbes  were tested for their L-methioninase activity and total protein content. The  results indicated a new strain of Bacillus, identified as Bacillus cucumis  LAKHS12, exhibiting the highest L-methioninase activity. The cytotoxic activity  on in-vitro cancer cell lines by MTT assay revealed that L-methioninase from B.  cucumis exhibited highest cytotoxicity. The percentage viability of cervical  cancer Hela cells was 35.7%, indicating a significant cytotoxicity of 64.3% for 48  h of treatment with L-methioninase at a lowconcentration. This finding was  further supported by the microscopic observations of treated cancer cells. It can  be concluded that the isolate has potential for further enzyme purification,  characterization, and anticancer applications.
Keywords: Bacillus cucumis; cancer; L-methioninase; methionine dependency; MTT assay